Proprioceptive neuromuscular facilitation (PNF) stretching in futsal sport: How does it affect recovery pulse rate after high intensity interval training? - Haidar, Muhammad Daffa; Dewantara, Julian; Agustina, Dina; Nugroho, Sigit; Sumaryanti, Sumaryanti; Eken, Ã–zgÃ¼r; StojanoviÄ‡, Stefan (Tanjungpura Journal of Coaching Research, 2024)
Background and Study Aim. During exercise, the work of the heart will be controlled by sympathetic nerves that will regulate the frequency of heart rate through the depolarization effect. Faster changes in depolarization effects can affect action potentials that become more frequent, so that the heart rate will increase. Stretching serves to improve blood flow and circulation, so it can help in lowering the pulse rate. This study aims to determine the effectiveness of PNF stretching on pulse rate recovery after doing HIIT on futsal players.Material and Methods. This research is an experimental research with the design of this research is control group pretest-posttest consisting of 20 people with sampling technique using population sampling. They were divided by ordinal pairing into two groups, namely the PNF stretching group and the control group. The PNF stretching group underwent PNF stretching session after HIIT session, while the control group only did HIIT session without PNF stretching. Recovery pulse rate was measured before and after the HIIT session, as well as after the PNF stretching intervention or rest period for the control group. Analysis was assisted using SPSS 26.Results. The results showed a significant decrease in recovery pulse rate in the experimental group with an average pretest value of 75.6, posttest 86.8 (p=0.000) with an effectiveness value of 85.8%. The control group showed a less significant decrease in recovery pulse rate, with an average pretest value of 75.2, posttest 76.8 (p=0.104) with an effectiveness value of 75.8%.Conclusion. So that this research is expected to serve as material for consideration, reference, and knowledge for parties related to the world of sports and health science, especially the effectiveness of Proprioceptive Neuromuscular Facilitation (PNF) stretching on pulse recovery after doing High Intensity Interval Training (HIIT).